The Demonology in the Environment of the New Testament: An Ideological/ Conceptual Analysis of the Word daimōn in the Corpus Hermeticum - Pessoa de Lira, David (2011)
When one speaks about ideas and concepts of a word, they refer to a set of traditions which serve as presuppositions for the formation of such ideas and concepts. The World of the New Testament was built of varied traditions which substantiated the philosophical and theological idea and reasons. In order to understand the world of the New Testament, it is necessary to understand the similarities and the differences among them and the correlations among these several traditions. The present text aims to analyze the ideas and the concepts concerning to the use of the word daimōn in the religious environment of the Graeco-Roman World, so that their senses are clarified without the senses given to the daimones by the Christianity and Judaism. The analysis procedure takes into account the analogy or the comparison of religious traditions of the same context and the development of the sense that the word daimōn assumed in the course of the religious history. Considering this presupposition, it is important to proceed to an analysis of the demonology present in the Corpus Hermeticum, so that it is possible to understand the idea concerning to the word daimōn in the religious environment of the Hellenistic/Roman World. It is necessary to point out that the word daimōn employed in the Corpus Hermeticum retakes its primitive sense of a genius, good and evil spirit, guardian of the destiny established by the regent gods or a divine energy. In a second stage, it is necessary to identify some senses and changes of meanings of this word in the Jewish context of the Hellenistic period. And, for last, it is important to present the demonology of the Corpus Hermeticum.